Implementation of the Additive Ratio Assessment (ARAS) Method for Employee Performance Assessment in the Office of Perum Bulog - Yilistriyani; Indra Kanedi; Lena Elfianty (Penerbit ADM, 2021)
Employee Performance Appraisal is very important, especially for employees in the scope of Perum BULOG Divre Bengkulu to encourage motivation and professionalism of employees in improving work quality. Constraints faced in conducting performance appraisals are due to the diversity of educational backgrounds, experiences, competencies and employee portfolios, so we need a system that can assist in the performance appraisal process so that the Employee Performance Appraisal does not become slow and experience difficulties. In the process of designing an employee performance appraisal decision support system application design uses the ARAS approach. The ARAS (Additive Ratio Assessment) method is one of the multicriteria decision-making methods based on the ranking concept using the utility degree, namely by comparing the overall index value of each alternative to the overall index value of the optimal alternative. The system implementation uses the Visual Basic 2010 programming language and the method used in this research is the waterfall method. From the results of the tests carried out, it can be concluded that this decision support system can provide selected employee decisions which later can be used as a reference for determining the quality of employee performance.